(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The aim of this study was to find out the effects of raised serum uric acid level on perinatal and maternal outcome in cases of pregnancy-induced hypertension. One hundred pregnant women with gestational period beyond 28 weeks with pregnancy-induced hypertension-preeclampsia and eclampsia were included in this study and divided into two groups. Group A (n=65) patients with a serum uric acid level >6 mg/dL was compared to Group B (n=35) patients with a uric acid level <6 gm/dL. It revealed that high uric acid level in patients with pregnancy-induced hypertension was a risk factor for several maternal complications like postpartum hemorrhage (Group A, 12 cases; Group B, 7 cases), postpartum eclampsia (Group A, 7 cases; Group B, 3 cases), abruptio placentae (Group A, 6 cases; Group B, 2 cases), HELLP syndrome (Group A, 2 cases; Group B, no case) and pulmonary edema (Group A, 3 cases; Group B, no case). In case of perinatal outcome, the birth weight, intrauterine growth retardation, intrauterine death, stillbirth and neonatal death rate were worse in Group A 1.9 kg, 46, 19, 7 and 8 cases in comparison to Group B, where those were 2.1, 13, 6, 2, and 2 cases respectively. In conclusion, high uric acid in blood in patient with hypertensive disorders in pregnancy is a risk factor for several maternal complications.